PERAN SERTA MASYARAKAT DALAM PENCEGAHAN DAN PEMBERANTASAN TINDAK PIDANA KORUPSI - Kamal, Muhammad; Arifin, Muhammad Yarif (Fakultas Hukum Universitas Muhammadiyah Magelang, 2019)
The leading cause of corruption in the regions is the enormous power in the hands of the local elite. However, the amount of authority held by the regions is not accompanied by an active control function through oversight institutions that involve the community. This study aims to analyze community involvement in the prevention and eradication of corruption in Indonesia. This research is normative legal research with a doctrinal approach. In a democratic country like Indonesia, community participation is needed in the prevention and eradication of corruption. Public participation in efforts to prevent and eradicate criminal acts of corruption is manifested in the form of data search, acquisition, and provision of data on corruption. In addition, the community has the right to provide advice and opinions responsibly for the prevention and eradication of corruption.